2008
DOI: 10.17660/actahortic.2008.801.101
|View full text |Cite
|
Sign up to set email alerts
|

Vapour Removal From the Greenhouse Using Forced Ventilation When Applying a Thermal Screen

Abstract: The objective of this study is to dimension a system capable of removing water vapour mainly generated by evaporation of the crop when a thermal screen is applied. The humid greenhouse air is replaced by cold dry outside air using an air distribution system. The dry air is injected above the greenhouse floor thereby forcing humid air to pass through the thermal screen. The excess air in the greenhouse will flow away though leaks in the cover. The common procedure to remove moisture from the greenhouse where a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…The combination with forced ventilation extended the possibilities to use the screens because screens can be kept closed without vapour problems. This was expected and in accordance with the research of Campen (2008), who proved that also with a double screen forced ventilation contributes to control of humidity.…”
Section: Discussion: Limitations and Applicationssupporting
confidence: 91%
See 1 more Smart Citation
“…The combination with forced ventilation extended the possibilities to use the screens because screens can be kept closed without vapour problems. This was expected and in accordance with the research of Campen (2008), who proved that also with a double screen forced ventilation contributes to control of humidity.…”
Section: Discussion: Limitations and Applicationssupporting
confidence: 91%
“…Recently, model studies were used to evaluate new ways for energy saving (Elings et al, 2005;Campen, 2008). However, these studies did not result in an integrated approach for commercial cultivation with a low energy requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The boundary conditions of wind speed distribution are deduced from experimental data and wind direction with respect to the longitudinal axis of the greenhouse, which can range from 0 to 90°. Roy and Boulard (2005) simulated the impact of wind at 45 and 90°, showing the influence of wind direction in the air velocity, temperature and humidity distributions inside the greenhouse; a similar result was found by Campen (2008). Rico-García et al (2006) also showed that a greenhouse with large vertical roof windows works better with a windward condition, whereas the multi-span greenhouse works better with a leeward condition.…”
Section: Windward and Leeward Wind Directionsupporting
confidence: 55%
“…According to Majdoubi et al (2009), reorienting crop rows in simple ways improved climatic Figure 5. Schematic diagram of the system in which the ventilator is located at the sidewall of the greenhouse, drawing in outside air and distributing it via ducts (Campen et al, 2008).…”
Section: Incorporation and Crop Modellingmentioning
confidence: 99%
“…Roy et al (2008) studied moisture on the surface of leaves at low light levels; crop transpiration and air flow were integrated into a single parameter model of leaf stomatal response to air flow and radiation. Campen (2008) showed that climate through a ventilation system is more homogeneous and the control is more efficient than with the conventional method of steam extraction. Dehumidifiers and cooling reduce the overall difference in humidity between the middle and lower areas of a greenhouse, as demonstrated by Kim (2008) using a 3D model could identify the heterogeneous distribution of relative humidity in a greenhouse.…”
Section: Incorporation Crop Effects and Crop Modelingmentioning
confidence: 99%